Evaluasi Usability Aplikasi Android Dharmadana Menggunakan Metode End User Computing Satisfaction (EUCS) - I Made Sugi Ardana (Syntax Idea)
Dharma Dana is an obligation of Hindus of 5% of income in accordance with the Bhisama Sabha Pandita Parisada concerning the fund. The amount of the Dharma Fund that is deposited to the Badan Dharma Dana Nasional (BDDN) is 2.5% of income. Parisada Hindu Dharma Indonesia Pusat as the supreme assembly for Indonesian Hinduism has the goal of creating a Hindu society with high belief, commitment and loyalty to the teachings of Hinduism towards physical and spiritual well-being. To make it easier for people to make funds (donations), an android-based application was created with the name Dharmadana application. Android applications are currently developing very quickly and have become an alternative media that can be used to convey the information needed by customers without any time or place limitations. One model for evaluating this android application is End User Computing Satisfaction (EUCS). EUCS is a method for measuring the level of satisfaction of users of an application system by comparing the expectations and reality of an application. The EUCS evaluation model was developed by Doll & Torkzadeh. Evaluation using this model places more emphasis on end user satisfaction with technological aspects based on 5 (five) dimensions, namely content dimensions, accuracy dimensions, format dimensions, ease of use dimensions, and dimension of timeliness. The results showed that most of the Dharmadana applications (68.42%) were installed by generation X (born 1960 to 1980). The quality of the application on a scale of 5 for the content dimension is very good (average score 4.14) while for other dimensions the quality is good. The dimensions of accuracy score 3.82, format score 3.87, ease of use score 3.91, and timeliness score 4.00. Quality needs to be improved for application features on dimensions with score good.